Single causality and crisis theory: a reply to David Harvey - Roberts, Michael (Geografares, 2019)
Michael Roberts offers a comprehensive critique of Harvey and argues that Marx never abandoned the TRPF as a relevant explanation of crises. He never went back to the theory in his later years simply because he was satisfied with it. Rather than developing the theory he tried to figure out how to use it to explain the cyclical nature of capitalism as well as its transitory nature. Roberts contends that Marx’s assumptions for the TRPF are realistic and can be reduced to just two: labor power is the only source of value, and capital accumulation leads the organic composition of capital to rise. He argues against the view that each crisis has a different or ‘conjunctural’ origin. The recurrent nature of capitalist crises implies that they must have a common cause.Translator: Cássio Arruda Boechat (cassio.boechat@ufes.br)
Keywords: Translation of Single causality and crisis theory: a reply to David Harvey by Michel Roberts